2002
DOI: 10.1143/jpsj.71.905
|View full text |Cite
|
Sign up to set email alerts
|

Unconventional Superconductivity and Josephson Effect in Superconductor/Dirty Normal Metal/Superconductor Junctions

Abstract: A relation between amplitudes of Josephson current and nodes in excitation-gap of unconventional superconductors is studied in superconductor/dirty normal metal/superconductor junctions. It is found that ensemble average of the Josephson current vanishes when the junction interface is perpendicular to a plane which includes line-or point-zeros of the excitation-gap. A zero-energy state formed at the junction interface is a character of unconventional superconductor junctions and causes large sample-tosample fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(20 citation statements)
references
References 26 publications
(37 reference statements)
1
19
0
Order By: Relevance
“…80 It is interesting to study effects of impurities on transport properties in spin-triplet superconductor junctions. 46,78,81,82,83,84,85,86,87,88,89,90,91,92,93,94 V. CONCLUSION We have discussed effects of impurity scatterings on the conductance in normal-metal/d wave superconductor junctions. The conductance is calculated from the Andreev and the normal reflection coefficients which are estimated by using the single-site approximation.…”
Section: Discussionmentioning
confidence: 99%
“…80 It is interesting to study effects of impurities on transport properties in spin-triplet superconductor junctions. 46,78,81,82,83,84,85,86,87,88,89,90,91,92,93,94 V. CONCLUSION We have discussed effects of impurity scatterings on the conductance in normal-metal/d wave superconductor junctions. The conductance is calculated from the Andreev and the normal reflection coefficients which are estimated by using the single-site approximation.…”
Section: Discussionmentioning
confidence: 99%
“…Actually, the low-temperature anomaly of the Josephson current has been reported [15][16][17][18]24,25 in SIS junctions of these symmetries. The absence of the proximity effect in diffusive normal metals is described by a relation [26][27][28] …”
Section: Pairing Symmetriesmentioning
confidence: 99%
“…In fact, one of authors has shown that the ensemble average of the Josephson current vanishes in diffusive SNS junctions for several unconventional superconductors. 26,27 This phenomenon is now interpreted as the absence of the proximity effect in diffusive normal metals. 28,29 On the other hand, two of us discussed anomalous enhancement of the zero-bias tunneling conductance due to the proximity effect in the presence of the MARS.…”
Section: Introductionmentioning
confidence: 97%
“…Recently, it was shown that the Josephson current in TS/ DN/TS junctions 18 is strongly enhanced at low temperatures and is proportional to sin͑⌿ /2͒, where ⌿ is a superconducting phase difference between left and right superconductors. 19 These results are quite different from those for d-wave superconductor/DN/d-wave superconductor junctions.…”
Section: Introductionmentioning
confidence: 99%